CLINICAL TRANSPLANTATION, ARTIFICIAL ORGANS, REGENERATIVE MEDICINE AS THREE COMPONENTS OF A SCIENTIFIC SPECIALTY (VIII All-Russian congress of transplantologists) - O. P. Shevchenko; E. A. Stakhanova (Вестник трансплантологии и искусственных органов, 2017)
.